Representable and unrepresentable in film art: the limits of visual representation of reality - Lučić, Krunoslav (Poznańskie Studia Slawistyczne, 2025)
The paper focuses on the limitations of the cinematic representation of reality. Since the film was initially understood as an innovative tool for the reproduction of reality, but also as a copy of the viewer’s perception, the paper analyzes the historical views on the media’s inability to imitate reality, and how it becomes a means of artistic design. To that extent, the first part of the paper deals with the distinguishing factors that prevent the film from being a record of reality, such as framing, reduced depth, or editing. Then the focus is placed on the strategies of visual display that played a key role in the avant-garde film, exploiting the stylization potential of the medium. This part also highlights the possible thematic limitations in the form of presenting mental states or socially taboo phenomena. Finally, the emphasis is placed on cinematic attempts to fully depict reality through realistic strategies using its properties such as infinity, indeterminacy and randomness.